Analysis of Job Design and Work Culture on Employee Performance (Case Study at Bank Btpn, Bawakaraeng Makassar Branch) - Fitri Handayani (Pustaka Digital Indonesia, 2022)
This study aims to determine: (1) the effect of job design on employee performance, (2) the influence of work culture on employee performance. This research method used is quantitative, this research is a study that collects data or information and states variables that describe job design and work culture on employee performance. Woth a total sample of 80 respondents taken from the entire population. The instrument used in this study was a questionnaire sheet. Management is carried out by means of the SPSS program comparison t test. The results of this study use several tests, one of which is the t test using the t test, one of which is the t test using the t test, with the t test it is known that the value of t count > t table, this indicates that the hypothesis is accepted. The conclusions of the results of this study indicate that: (1) there is a significant positive effect between job design on employees from the results of the test, there is it count 0.5480 > t table 1.990 (2) there is no significant positive influence between work culture on performance at the Bawakaraeng Branch Bank From the test result t count -1.787 <t table 1.990.